The American Midwest in film and literature : nostalgia, violence, and regionalism - Ochonicky, Adam R. (Indiana University Press, 2020)
Adam R. Ochonicky gives a critical overview of the Midwest's symbolic and often contradictory meanings in film and literature. Starting with the frontier writings of Frederick Jackson Turner, this book examines Midwestern film and literary texts stretching from the late-19th century through the beginning of the 21st century.